(untitled) (Research, Society and Development, 2023)
Palliative care is indicated in the face of a disease that poses a risk of death and aims to improve the quality of life of the patient and their families. The objective of this work is to understand and discuss the communication of bad news in the context of palliative care. The work was carried out through an integrative literature review, through the search and analysis of the scientific production of the international literature. It sought to answer which professional category is most responsible for transmitting bad news and what are the difficulties encountered by professionals involved in this process. The results showed that the professional category that most communicates bad news is that of doctors, leaving nurses in second place. In addition, nursing professionals, for the most part, find difficulties in the process of transmitting the bad news, getting stuck in dilemmas of the profession. It is concluded that these professionals need psychological support in order to minimize the damage caused by the assistance provided by them.